Disparities in safe sex counseling & behavior among individuals with substance dependence: a cross-sectional study - D'Amore Meredith M; Cheng Debbie M; Allensworth-Davies Donald; Samet Jeffrey H; Saitz Richard (BMC, 2012)
Abstract Background Despite the vast literature examining disparities in medical care, little is known about racial/ethnic and mental health disparities in sexual health care. The objective of this study was to assess disparities in safe sex counseling and resultant behavior among a patient population at risk of negative sexual health outcomes. Methods We conducted a cross-sectional analysis among a sample of substance dependent men and women in a metropolitan area in the United States. Multiple logistic regression models were used to explore the relationship between race/ethnicity (non-Hispanic black; Hispanic; non-Hispanic white) and three indicators of mental illness (moderately severe to severe depression; any manic episodes; ≥3 psychotic symptoms) with two self-reported outcomes: receipt of safe sex counseling from a primary care physician and having practiced safer sex because of counseling. Results Among 275 substance-dependent adults, approximately 71% (195/275) reported ever being counseled by their regular doctor about safe sex. Among these 195 subjects, 76% (149/195) reported practicing safer sex because of this advice. Blacks (adjusted odds ratio (AOR): 2.71; 95% confidence interval (CI): 1.36,5.42) and those reporting manic episodes (AOR: 2.41; 95% CI: 1.26,4.60) had higher odds of safe sex counseling. Neither race/ethnicity nor any indicator of mental illness was significantly associated with practicing safer sex because of counseling. Conclusions Those with past manic episodes reported more safe sex counseling, which is appropriate given that hypersexuality is a known symptom of mania. Black patients reported more safe sex counseling than white patients, despite controlling for sexual risk. One potential explanation is that counseling was conducted based on assumptions about sexual risk behaviors and patient race. There were no significant disparities in self-reported safer sex practices because of counseling, suggesting that increased counseling did not differentially affect safe sex behavior for black patients and those with manic episodes. Exploring the basis of how patient characteristics can influence counseling and resultant behavior merits further exploration to help reduce disparities in safe sex counseling and outcomes. Trial registration NCT00278447